Stepanovna's Motivation in Marriage Proposal Script by Anton Chekov - Sagita Octavia; Singgih Daru Kuncara; Indah Sari Lubis (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
This research focuses on motivation in Marriage Proposal script by Anton Chekov which was published in 1888. The script tells about a rich woman named Stepanovna who was proposed by a rich man named Lomov. However, the proposal did not go smoothly because Stepanovna was long-winded about it. Therefore, this study aims to determine the motivation of Stepanovna, by describing Reaske’s motivation theory to reveal the type of motivation in Stepanovna. Then, the theory used in analyzing Stepanovna’s character, the researcher used Boggs and Petri characterization theory. Furthermore, the researcher used qualitative research as the method and mimesis as the approach in this research. The data collected comes from the dialogue of Stepanovna and the narration of Marriage Proposal script. The results showed that there were four types of seven types of motivation they are fear of failure, love, hope for reward, and jealousy. In four types of motivation, the researcher got four characters of Stepanovna, they are an arrogant, determined, aggressive and sincere person. It can be concluded that the characters of Stepanovna were influenced by her motivations, it means that these characters depending the situation faced by Stepanovna and made Stepanovna behave towards Lomov then it is the reason of her motivation existed